Online Shopping Experience Drives Online Shopping Intention: Role of Omnichannel Shopping Trust - Marinao-Artigas, E (Fundacao Escola de Comercio Alvares Penteado, 2025)
Purpose – This study proposes a model in which online shopping intention is a consequence of the online shopping experience in an omnichannel environment. Theoretical framework – The experience is shaped by the interaction between a consumer’s cognitive and emotional experiences, with omnichannel shopping trust playing a crucial mediating role in the relationship between online shopping experience and purchase intention. The theoretical model is based on the Stimulus-Organism-Response (S-O-R) framework. Design/methodology/approach – Data analysis was performed using structural equation model analysis. Systematic random probability sampling was used to recruit 600 consumers, all of whom had experience with omnichannel shopping in Chilean retail settings. Findings – Online shopping intention results from the interaction between cognitive and emotional experiences. Omnichannel shopping trust partially mediates the effect of the online shopping experience on purchase intention. Practical & social implications of research – This study has important implications for digital platform managers and retailers who want to deliver an optimal omnichannel experience. Originality/value – In an omnichannel environment, the retailer needs to establish a strong connection through the cognitive and emotional experience of the shopper. © 2025, Fundacao Escola de Comercio Alvares Penteado. All rights reserved.